2012
DOI: 10.1002/eji.201142298
|View full text |Cite
|
Sign up to set email alerts
|

Siglec‐7 tetramers characterize B‐cell subpopulations and leukemic blasts

Abstract: Cell surface glycosylation has important regulatory functions in the maturation, activation, and homeostasis of lymphocytes. The family of human sialic acid-binding immunoglobulin-like lectins (siglecs) comprises inhibitory as well as activating receptors intimately involved in the regulation of immune responses. Analyses of the interaction between siglecs and glycans are hampered by the low affinity of this interaction. Therefore, we expressed siglec-7 in eukaryotic cells, allowing for glycosylation, and olig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Several efforts have been made to increase multivalency of Siglecs. For example, biotinylation of monomeric Siglec-7 to create tetramers with Streptavidin 33 , pre-complexing Siglec-Fcs with αhIgG1 12 , and pentameric comp constructs of Siglecs to detect Siglec-8 and -9 ligands 13 . Taking this a step further, we have demonstrated that tetramerization of dimeric Siglec-Fc chimeras provides greatly enhanced sensitivity for detecting sialic acid ligands on cells and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Several efforts have been made to increase multivalency of Siglecs. For example, biotinylation of monomeric Siglec-7 to create tetramers with Streptavidin 33 , pre-complexing Siglec-Fcs with αhIgG1 12 , and pentameric comp constructs of Siglecs to detect Siglec-8 and -9 ligands 13 . Taking this a step further, we have demonstrated that tetramerization of dimeric Siglec-Fc chimeras provides greatly enhanced sensitivity for detecting sialic acid ligands on cells and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…typically assessed by studying binding of recombinant GBPs to synthetic arrays containing a broad collection of defined glycan structures chemically linked to an inert surface (18,19). Glycan arrays are useful tools that can point toward a class of isolated glycan structures that may form components of a biological binding motif.…”
Section: Significancementioning
confidence: 99%
“…Knowledge about Siglec expression and function on NK cell subsets is still limited in terms of NK cell differentiation and maturation, and the role of Siglec ligand-receptor interactions in disease remains to be explored. Whether Siglec-7 and -9 ligands in human cancer are expressed on malignant or healthy cells is a subject of controversy (3,(25)(26)(27)(28), as is the related question as to whether absence of inhibitory Siglecligand interactions promotes or inhibits tumor progression, either by uncoupled immune stimulation or by inhibition of immune defense (10,(25)(26)(27). Here, we found that Siglec-7 and -9 ligands were significantly overexpressed on a broad range of human malignant cells of different histological types and that surface Siglec-7 and -9 ligand expression determined cytotoxicity of human primary NK cells against both NK cell-susceptible and -resistant tumor cells.…”
Section: Introductionmentioning
confidence: 99%